" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Verified answer
[Pembahasan]f(x) = x + 2
→ invers fungsi f(x)
f(x) = x + 2 → f'(x) = x - 2
↔nilai fungsi g(x)
(g • f) (x) = 2x² + 4x + 1
g(f(x)) = 2x² + 4x + 1
g(x) = 2(x - 2)² + 4(x - 2) + 1
g(x) = 2(x² - 4x + 4) + 4x - 8 + 1
g(x) = 2x² - 8x + 8 + 4x - 8 + 1
g(x) = 2x² - 4x + 1
☣---------------------------------------------------------------------------------------------------- ☣
◽ Kelas : 10
◽ Mapel : Matematika
◽ Kategori : Fungsi Komposisi
◽ Kata Kunci : Invers, Fungsi